A covalently cross-linked hyaluronic acid/bacterial cellulose composite hydrogel for potential biological applications. (15th January 2021) - Tang, Shuo; Chi, Kai; Xu, Hui; Yong, Qiang; Yang, Jian; Catchmark, Jeffrey M.
Graphical abstract: Highlights: BC and HA were covalently crosslinked by BDDE. Crosslinked BC/HA composites exhibited a denser and smoother surface. BDDE crosslinking improved water retention capability, dimensional stability, and elongation at break of BC/HA composites . Crosslinked BC/HA composites significantly promoted cell proliferation. Abstract: Bacterial cellulose (BC) is a good material candidate for wound dressing because of its fine 3-D network structure, high mechanical strength and water holding capability, and good biocompatibility. In this study, a composite hydrogel was prepared by using 1, 4-butanediol diglycidyl ether (BDDE) to cross-link BC and hyaluronic acid (HA). Cross-linked BC/HA composites exhibited a denser and smoother surface. This dense morphology improved water retention capability and dimensional stability. BDDE cross-linked BC/HA composite with 2% HA and 1% BDDE showed better overall properties, including water stability (12.7 % water solubility), mechanical properties (tensile strength: ∼ 0.61 MPa and Young's modulus: ∼1.62 MPa) and thermal stability (maximum degradation temperature: 360 °C), as compared to BC/HA without crosslinking. In addition, cell toxicity assays and morphology indicated the BDDE cross-linked BC/HA composite significantly promoted cell proliferation and adhesion. This chemically cross-linked BC/HA composite may have many new biomedical applications in wound care.